Measuring the Success of Women Led “Dry Zone Home Gardening” Program with Organic Amendments in Sri Lanka - T M Kularathne; Pathmanathan Sivashankar; W G.C Wekumbura (Agricultural Socio-Economics Journal, 2019)
This paper attempts to measure the level of success of the dry zone home gardening (HG) program introduced by the government of Sri Lanka among the women.  The women used the organic amendments for their HG activities. This study assessed the success of the program and the constraints faced in engaging in home gardening using organic amendments, and solutions to overcome were identified. Using an interviewer administrated structured questionnaire and purposive sampling technique, data were collected from 80 beneficiaries in Thirappane DS division. The results revealed that the beneficiaries were mainly married, unemployed, with no primary education and in more than 50 years’ age category. There was significant relationship between two socio-economic factors, farming factors, reasons to engage in home gardening with organic amendments, and outcomes of the program. Majority of women perceived that all the purposes of the program were successfully achieved. But 91.25 % of women have no idea on farming with organic amendments at large scale. Most influencing reason was the resulting low productivity with organic amendments. To address these solutions, the government should intervene to build the large scale farming with organic amendments in Anuradhapura district.